Modelling and simulation of complex repetitive construction operations. (2017) - Zaneldin, Essam
In an effort to improve productivity and optimise resource use, a simplified activity-on-arrow (AOA) approach is used in this paper to model and simulate real-world repetitive construction operations of high-rise buildings. The objective of the paper is to use simulation to find the optimum combination of construction resources to improve construction productivity and minimise operational cost. In order to achieve the goals of the study, a simulation model for typical floor finishes activities of a high-rise building project was developed. The model was validated through a predefined construction operation. Several model runs were then conducted using different resource combinations. The results were tabulated to arrive at the optimum combination that improves productivity and reduces the operational cost. In addition, the developed model was used to experiment with different resource alternatives and overtime options for one floor and for repetitive floors in order to arrive at the best resource alternatives that provide the optimum solution. The potential of using this approach for resource optimisation of large infrastructure networks is investigated, and possible future extensions to the present study are discussed.